1994
DOI: 10.1021/bi00197a004
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Ca2+-Deficient EF-Hand Governs the Phenotype of the Cardiac-Skeletal TnC-Chimera in Solution by Sr2+-Induced Tryptophan Fluorescence Emission

Abstract: In the development of force during Sr2+ activation, phenotypically cardiac muscle is more sensitive than fast-twitch skeletal muscle, and TnC is central in this mechanism. The uncertainty has remained, however, whether such functional manifestations in situ relied critically on protein-protein interactions in the fiber or whether the Sr2+ sensitivities were governed intrinsically within the TnC molecule. To resolve this, we substituted a tryptophan for phenylalanine-26 in both rabbit sTnC (sTnC.W26) and in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…In a similar chimeric TnC in which the inactive Ca2+ binding loop I was activated to chelate Ca2+ by genetic modification, the cardiac-type Sr2+ sensitivity was found to transform into the skeletal-type (Gulati and Rao, 1994). Taken together, the present results and those of previous studies strongly suggest that flexible loop I, in which the side chains are not coordinated to a metal ion, may be essential as part of the trigger mechanism in cardiac muscle.…”
Section: Discussionsupporting
confidence: 73%
“…In a similar chimeric TnC in which the inactive Ca2+ binding loop I was activated to chelate Ca2+ by genetic modification, the cardiac-type Sr2+ sensitivity was found to transform into the skeletal-type (Gulati and Rao, 1994). Taken together, the present results and those of previous studies strongly suggest that flexible loop I, in which the side chains are not coordinated to a metal ion, may be essential as part of the trigger mechanism in cardiac muscle.…”
Section: Discussionsupporting
confidence: 73%
“…It is suggested that this low-temperature effect could increase the activation energy required to trigger the conformational response (42). Full-length mammalian sTnC is 66.7% identical in amino acid sequence to mammalian cTnC, and the two isoforms display distinct functional differences (1,17,18,20,39) and differ in the number of functional Ca 2ϩ binding sites. For these reasons, prediction of how lowered environmental temperature would affect the structure of mammalian cTnC from data on sTnC is tenuous.…”
Section: Discussionmentioning
confidence: 99%
“…Both the normal and tryptophan 26 derivatives of skeletal TnC (sTnC4 and sTnC4.W), the cardiac/skeletal chimera with Ca2+-deficient site I (cl/s and cl/s.W), and the Ca2+binding variants (CBcl/s and CBcl/s.W) were the same as before (Gulati & Rao, 1994). The tryptophan derivative of sTnC-, an inactive skeletal TnC in which site I was made Ca2+-deficient by replacing the putative x-coordinate in the skeletal EF-hand [see Kretsinger (1980)] from Asp27-* Ala, was generated especially for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The codon for tryptophan was inserted in position 26 by replacing that for phenylalanine, exactly as in the other constructs. Because no tryptophan existed in bovine cTnC or rabbit sTnC, Trp26 provided a ready spectroscopic marker that could be followed with ease (Gulati & Rao, 1994). The nucleotide sequences of the mutants were verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation